Deep brain stimulation induces BOLD activation in motor and non-motor networks: An fMRI comparison study of STN and EN/GPi DBS in large animals - Min, Hoon-Ki (2012)
The combination of deep brain stimulation (DBS) and functional MRI (fMRI) is a powerful means of tracing brain circuitry and testing the modulatory effects of electrical stimulation on a neuronal network in vivo. The goal of this study was to trace DBS-induced global neuronal network activation in a large animal model by monitoring the blood oxygenation level-dependent (BOLD) response on fMRI. We conducted DBS in normal anesthetized pigs, targeting the subthalamic nucleus (STN) (n=7) and the entopeduncular nucleus (EN), the non-primate analogue of the primate globus pallidus interna (n=4). Using a normalized functional activation map for group analysis and the application of general linear modeling across subjects, we found that both STN and EN DBS significantly increased BOLD activation in the ipsilateral sensorimotor network (FDR < 0.001). In addition, we found differential, target-specific, non-motor network effects. In each group the activated brain areas showed a distinctive correlation pattern forming a group of network connections. Results suggest that the scope of DBS extends beyond an ablation-like effect and that it may have modulatory effects not only on circuits that facilitate motor function but also on those involved in higher cognitive and emotional processing. Taken together, our results show that the swine model for DBS fMRI, which conforms to human implanted DBS electrode configurations and human neuroanatomy, may be a useful platform for translational studies investigating the global neuromodulatory effects of DBS.